Investigation of structural perfection of SiC ingots grown by a sublimation method - Avramenko, S.F.; Kiselev, V.S.; Valakh, M.Ya.; Visotski, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Monocrystalline SiC ingots were grown by a modified Lely method using 6H-SiC seed crystals with (0001) base plane. The crystal growth was carried out in the temperature range 2200-2500 ⁰C at Ar pressure from 2 to 40 mbar. The rate of growth varied between 0.3 and 1.5 mm/hour in the C-axis direction. At growth time of about 15 hours we obtained the ingots with 35 mm useful diameter. To determine the polytype composition of SiC ingots the Raman scattering technique was used. The structural defects were investigated by means of reflection and transmission light microscopy and by selective etching. In the best ingots the dislocation density did not exceed 102 cm⁻², the micropipe density - 10-20 cm⁻², and blocks were absent.